Community Structure of Phytoplankton in The Waters of Gili Trawangan, North Lombok - Widia Apriani; Lalu Japa; Didik Santoso (Jurnal Biologi Tropis, 2023)
Gili Trawangan is one of the popular marine tourism destinations and conservation areas in the West Nusa Tenggara Province. Increased human activity in the Gili Trawangan is associated with increased pressure on aquatic ecosystems. Human activity pressure comes from tourism activities and negative impacts due to various community activities around the waters can reduce water quality. Changes to water quality can be seen from the abundance and composition of phytoplankton. This is because phytoplankton plays an important role in a water body, namely as a primary producer in the food chain and has the ability to respond to the changes of the environment factors. This rearch was conducted to determine the abundance and composition of phytoplankton community structure in Gili Trawangan, North Lombok. Seawater samples were taken using a 20 µm plankton net by filtering 100 L of water. The filtered water samples were then preserved using formalin in 4% concentration. Data were analyzed by calculating the abundance of individuals, diversity (H'), uniformity (E), and dominance (D). The results showed that the average abundance of phytoplankton species was 1026.296 Ind/L and 22 genera of phytoplankton were identified. Species diiversity index (H'=2.58) is classified as medium. Species uniformity index (E=0.88) and species dominance index (C=0.10). Based on the results of this research it can be concluded that the waters of Gili Trawangan North Lombok are classified as oligotrophic waters.